STUDI KASUS: PENTINGNYA ASUHAN KEBIDANAN KOMPREHENSIF UNTUK MENCEGAH DAN MENGATASI BENDUNGAN ASI PADA IBU POSTPARTUM - Meilany Laisouw; Ratna Malawat (Jurnal Kebidanan, 2022)
Breast engorgement is one of the problems that often occurs during puerperium. Many factors can affect the occurrence of breast engorgement, including the lack of breastfeeding intensity, no breast care during pregnancy, abnormalities in the nipples and the lack of knowledge of the mother. Breast engorgement will greatly affect the fulfillment of the babies needs for breastmilk which is the only best food for them to help their growth and development. This case study describes how the occurrence of breast engorgement and the efforts to deal with it in Mrs. S, a 22-years-old primipara. The efforts to handle breast engorgement in this case were carried out by teaching the Mrs. S and her family how to care for breast and nipples, how to breastfeed properly, and providing education to increase her knowledge. The midwifery care provided can help Mrs. S to overcome breast engorgement and breastfeed her baby normally. Midwifery care related to preparation for breastfeeding needs to be carried out from pregnancy to postpartum period comprehensively. Thus, mothers can prevent and overcome breastfeeding problems independently so that exclusive breastfeeding for six months can be achieved.